CLMP Promotes Leukocyte Migration Across Brain Barriers in Multiple Sclerosis. Issue 6 (9th November 2022) - Fournier, Antoine Philippe; Zandee, Stephanie; Charabati, Marc; Peelen, Evelyn; Tastet, Olivier; Alvarez, Jorge Ivan; Kebir, Hania; Bourbonnière, Lyne; Larouche, Sandra; Lahav, Boaz; Klement, Wendy; Tea, Fiona; et al.
Abstract : Background and Objectives: In multiple sclerosis (MS), peripheral immune cells use various cell trafficking molecules to infiltrate the CNS where they cause damage.The objective of this study was to investigate the involvement of coxsackie and adenovirus receptor–like membrane protein (CLMP) in the migration of immune cells into the CNS of patients with MS. Methods: Expression of CLMP was measured in primary cultures of human brain endothelial cells (HBECs) and human meningeal endothelial cells (HMECs), postmortem brain samples, and peripheral blood mononuclear cells (PBMCs) from patients with MS and controls by RNA sequencing, quantitative PCR, immunohistochemistry, and flow cytometry. In vitro migration assays using HBECs and HMECs were performed to evaluate the function of CLMP. Results: Using bulk RNA sequencing of primary cultures of human brain and meningeal endothelial cells (ECs), we have identified CLMP as a new potential cell trafficking molecule upregulated in inflammatory conditions. We first confirmed the upregulation of CLMP at the protein level on TNFα-activated and IFNγ-activated primary cultures of human brain and meningeal ECs. In autopsy brain specimens from patients with MS, we demonstrated an overexpression of endothelial CLMP in active MS lesions when compared with normal control brain tissue. Flow cytometry of human PBMCs demonstrated an increased frequency of CLMP + B lymphocytes and monocytes in patients with MS, when compared with that in healthy controls. The use of a blocking antibody against CLMP reduced the migration of immune cells across the human brain and meningeal ECs in vitro. Finally, we found CLMP + immune cell infiltrates in the perivascular area of parenchymal lesions and in the meninges of patients with MS. Discussion: Collectively, our data demonstrate that CLMP is an adhesion molecule used by immune cells to access the CNS during neuroinflammatory disorders such as MS. CLMP could represent a target for a new treatment of neuroinflammatory conditions.